Phosphosilicate gel-polybenzimidazole nanocomposite novel membrane for fuel cell application - Ghosh, P. (Springer India, 2014)
Phosphosilicate gel-Polybenzimidazole (PBI) nanocomposite electrolyte membranes are synthesised, characterized and tested for fuel cell performance. The chemical structure of both phosphosilicate gel and PBI are confirmed by Fourier transform infrared spectroscopy. The Scanning electron microscope image of PBI shows the fibrous nature of the polymer. In particular, the effects of phosphosilicate gel powder that enhance membraneâs performance as an electrolyte in fuel cell are studied. The inorganic loading to PBI exhibits higher ion exchange, generates greater power and remains stable for higher temparature while used as an electrolyte in fuel cell. The performance of the membranes is tested for fuel cell at different operating temperature varying from 130Â Â°C to 170Â Â°C. At 150Â Â°C about 60Â enhancement of peak power generation and more than 1.5 times enhancement of thresold load current are achieved by using 5Â inorganic (PPSG) loading. Â© 2014, Central Institute of Plastics Engineering & Technology.